Factors Related to Visual Outcomes after Lens Surgery in Isolated Microspherophakia - Jialei Zheng; Lina Cheng; Zexu Chen; Tianhui Chen; Yongxiang Jiang (Journal of Ophthalmology)
Purpose. To evaluate the main factors influencing visual performance after lens subluxation surgery in subjects with isolated MSP. Design. Retrospective study. Methods. In this study, 38 eyes of subjects with isolated MSP (microspherophakia) were included and divided into two groups based on preoperative IOP (intraocular pressure), IOP <21 mmHg, or IOP ≧21 mmHg. Phacoemulsification and scleral-fixated modified capsular tension ring implantation were performed with or without goniosynechialysis according to the IOP. Some ocular biometric parameters, such as corneal curvature, corneal pachymetry, endothelial cell count (ECC), anterior chamber depth (ACD), and axial length, were evaluated. The best-corrected visual acuity (BCVA) and IOP of these subjects were measured before the surgery and during <1 month and 3- to 6-month postoperative follow-ups. Results. Compared with the high IOP group, the normal IOP group was significantly younger and had better preoperative BCVA, a higher ECC, deeper ACD, a lower postoperative IOP, and flatter total corneal refractive power K1. The multivariable analysis revealed that preoperative ACD (b = −0.113, t = −2.070, P=0.047) and preoperative BCVA (b = 0.153, t = 2.562, P=0.015) were significantly associated with postoperative BCVA at 3–6 months. A preoperative ACD of 1.86 mm was found to be the optimal cut-off point for 3- to 6-month postoperative BCVA of ≧20/63 (≤0.52 logMAR). Conclusions. In addition to the effect of normal IOP, better preoperative BCVA and deeper ACD also correlated with better visual outcomes after lens surgery. Preoperative ACD served as a warning for isolated MSP subjects, especially for the risk of irreversible loss of postoperative vision. This trial is registered with “ChiCTR2000039132.”